Energy System Modelling Challenges for Synthetic Fuels : Towards net zero systems with synthetic jet fuels. Issue 2 (1st April 2021) - Kim, Seokyoung; Dodds, Paul E.; Butnar, Isabela
Long-distance air travel requires fuel with a high specific energy and a high energy density. There are no viable alternatives to carbon-based fuels. Synthetic jet fuel from the Fischer-Tropsch (FT) process, employing sustainable feedstocks, is a potential low-carbon alternative. A number of synthetic fuel production routes have been developed, using a range of feedstocks including biomass, waste, hydrogen and captured carbon dioxide. We review three energy system models and find that many of these production routes are not represented. We examine the market share of synthetic fuels in each model in a scenario in which the Paris Agreement target is achieved. In 2050, it is cheaper to use conventional jet fuel coupled with a negative emissions technology than to produce sustainable synthetic fuels in the TIAM-UCL and UK TIMES models. However, the JRC-EU-TIMES model, which represents the most production routes, finds a substantial role for synthetic jet fuels, partly because underground CO2 storage is assumed limited. These scenarios demonstrate a strong link between synthetic fuels, carbon capture and storage (CCS) and negative emissions. Future model improvements include better representing blending limits for synthetic jet fuels to meet international fuel standards, reducing the costs of synthetic fuels and ensuring production routes are sustainable.